\[\boxed{\text{623\ (623).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[Запишем\ число\ 10m + n = 11x;\ \ \ \]
\[где\ x - частное\ при\ делении\]
\[10m + n\ \ на\ 11;\]
\[так\ как\ 10m + n\ делится\ на\ 11;\ \ \ \ \]
\[m = n:\ \]
\[(10m + n)(10n + m) =\]
\[= 11x \cdot 11x = 121x^{2} -\]
\[делится\ на\ 121.\]
\[\boxed{\text{623.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ (2a - b)(2a + b) + b^{2} =\]
\[= 4a^{2} - b^{2} + b^{2} = 4a^{2}\]
\[2)\ 10x^{2} + (y - 5x)(y + 5x) =\]
\[= 10x^{2} + y^{2} - 25x^{2} =\]
\[= y^{2} - 15x^{2}\]
\[3)\ 64m^{2} - (8m + 9)(8m - 9) =\]
\[= 64m^{2} - 64m^{2} + 81 = 81\]
\[= 16x^{2} - 49y^{2} + 49x^{2} - 16y^{2} =\]
\[= 65x^{2} - 65y^{2} = 65 \cdot \left( x^{2} - y^{2} \right)\]
\[= a^{2} + 3a - 2a - 6 + 36 - a^{2} =\]
\[= a + 30\]
\[= 3a^{2} - 3ab - 9a^{2} + 4b^{2} =\]
\[= - 6a^{2} - 3ab + 4b^{2}\]